COVID-19 and Kidney Transplantation: Epidemiology, Histopathological Presentation, Clinical Presentation and Outcomes, and Therapeutic Strategies - Maurizio Salvadori; Aris Tsalouchos (Transplantology, 2022)
Multiple case series of kidney transplant recipients with COVID-19 have shown increased mortality compared to nontransplant patients. To date, we do not have high-level evidence to inform immunosuppression minimization strategies in infected transplant recipients. Most centers, however, have adopted an early antimetabolite withdrawal in addition to other interventions. The epidemiological problem concerns also dialysis patients and waitlisted patients who have a higher COVID-19 infection diffusion with respect to kidney transplant recipients. Several factors influence mortality among kidney transplant recipients. Among these factors are the age, race, and comorbidity factors, such as hypertension, diabetes mellitus, obesity, and previous respiratory problems. Treatment is still limited. The only effective antiviral drug is remdesivir that should be administered before the development of the cytokine storm. Vaccination seems to be useful, but due to the concomitant immunosuppression limiting its efficacy, at least three or four doses should be administered.